2020
DOI: 10.1007/s15010-020-01438-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in people living with human immunodeficiency virus: a case series of 33 patients

Abstract: Introduction Data on people living with human immunodeficiency virus (PLWH) in the current SARS-CoV-2 pandemic are still scarce. This case series of 33 PLWH patients with COVID-19 reveals symptoms and outcome in this special population. Methods Retrospective analysis of anonymized data including age, gender, HIV-associated parameters, symptoms, and outcome. Results Three out of 32 patients with documented outcomes died (9%). 91% of the patients recovered and 76% have been classified as mild cases. All patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
257
6
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(289 citation statements)
references
References 27 publications
18
257
6
8
Order By: Relevance
“… 90 A more recent study by Härter et al investigated a retrospective and uncontrolled case series involving 33 HIV patients and found that symptomatic COVID-19 and HIV coinfected patients with viral suppression on ART do not exhibit higher morbidity and mortality compared with other patients. 91 This study also indicated that SARS-CoV-2 infections may still occur during darunavir-based treatment. Because of the limitations of these case studies, more rigorously designed clinical studies with larger patient cohorts and proper control groups are needed to demonstrate the vulnerability of HIV patients to SARS-CoV-2 and the effect of PI antiviral therapies on protecting this population.…”
Section: Protease Inhibitors In Covid-19-related Clinical Studiesmentioning
confidence: 63%
“… 90 A more recent study by Härter et al investigated a retrospective and uncontrolled case series involving 33 HIV patients and found that symptomatic COVID-19 and HIV coinfected patients with viral suppression on ART do not exhibit higher morbidity and mortality compared with other patients. 91 This study also indicated that SARS-CoV-2 infections may still occur during darunavir-based treatment. Because of the limitations of these case studies, more rigorously designed clinical studies with larger patient cohorts and proper control groups are needed to demonstrate the vulnerability of HIV patients to SARS-CoV-2 and the effect of PI antiviral therapies on protecting this population.…”
Section: Protease Inhibitors In Covid-19-related Clinical Studiesmentioning
confidence: 63%
“…No conclusions can be drawn with our data in this regard. Differences were observed with Casado's and Härter's cohorts [24] , [26] , both with a higher prevalence of tenofovir in their patient regimens (73% and 66.7% respectively). Our cohort, has a lower prevalence in TDF-containing regimen (14.8%), more similar to that of Gervasoni (42%)25.…”
Section: Discussionmentioning
confidence: 76%
“…Our data are even more similar to those described by Gervasoni et al [25] . Härter's cohort [26] has a similar mean age but showed higher severity, hospitalization, admission to ICU and mortality rates. However, differences are more difficult to assess with a smaller sample and in the absence of data related to subject comorbidities; the same limitations were found when comparing with the Wuhan [27] and New York [28] , [29] cohorts, both with a significantly higher median age.…”
Section: Discussionmentioning
confidence: 93%
“…There are also concerns that an appreciable reduction in the distribution of protective bed nets (75%) and medicines for treating malaria due to lockdown measures, combined with no media campaigns, could result in up to 18 million additional cases and up to 30,000 additional deaths in sub-Saharan Africa alone compared to 2018 (Cash and Patel, 2020;Krubiner et al, 2020;World Health Organisation, 2020c). Whilst the latest evidence suggests that HIV positive patients do not have a higher COVID-19 infection rate, or a significantly different disease course than HIV-negative individuals (Blanco et al, 2020;Guo et al, 2020;Härter et al, 2020;Tarkang, 2020), patients' fears of contracting COVID-19 when they attend clinics, as well as limited access to health facilities and treatment during lockdown, will negatively impact on treatment and adherence to medicines as well as initial diagnosis (Africa News, 2020a;Chaiyachati et al, 2014;Mbuagbaw et al, 2015;Jerving, 2020;Krubiner et al, 2020;Tarkang, 2020). Medicine supplies can potentially be addressed through differentiated service delivery and other programmes (Jerving, 2020;Tarkang, 2020;Wilkinson and Grimsrud, 2020).…”
Section: Consequences Of Lockdown and Other Measures To Prevent And Tmentioning
confidence: 99%